(untitled) (Orfeu, 2022)
This research sheds light on the stylistic elements originated from the region of Puna found in the Puneña N°. 2, Op. 45 by Alberto Ginastera for Solo Cello in order to supply cellists with the background needed for the interpretation of the piece. As a methodological procedure authors such as Aretz (2003, 2008), Aguilar (2007) and Falú (2011), Suárez Urtubey (1967, 1972, 2003) were studied with the goal of better understanding the folk music of the Puna Region and the life and work of Ginastera. From the bibliographical research suggestions were drawn for the cellist interested in the performance and study of the work.